PENERAPAN METODE MEMBACA BERPASANGAN BERBANTUAN MEDIA KARTU KATA WARNA UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA KELAS II SD NEGERI 1 SUSUT - Ni Luh Putu Sunarianingsih; Nurul Isnaini Fitriyana; I Wayan Numertayasa (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2026)
This study aimed to examine the improvement of students' reading skills through the implementation of the paired reading method assisted by colored word card media for second-grade students at SD Negeri 1 Susut. The participants consisted of 27 second-grade students of SD Negeri 1 Susut, Susut District, Bangli Regency. This study employed Classroom Action Research (CAR) based on the Kemmis and McTaggart model, which was conducted in two cycles consisting of planning, action, observation, and reflection. Data were collected through oral tests, written tests, and documentation. The data were analyzed using descriptive quantitative analysis by calculating the mean scores and the percentage of students' learning mastery. The results indicated that the implementation of the paired reading method assisted by colored word card media improved students' reading skills. The mean score increased from 68.00 in the pre-test with a learning mastery percentage of 33.33% to 77.59 in Cycle I with 62.96% mastery, and further increased to 85.63 in Cycle II with 85.19% mastery. These findings indicate that the research success indicator was achieved. In addition to improving learning outcomes, the method also enhanced reading fluency, pronunciation accuracy, self-confidence, student participation, and learning motivation during the instructional process. Therefore, this method can serve as an alternative instructional strategy to improve elementary school students' reading skills.